2018
DOI: 10.1017/s0021859618000990
|View full text |Cite|
|
Sign up to set email alerts
|

Feathering rate impact on growth and slaughter traits of Japanese quail

Abstract: A total of 1180 1-day-old Japanese quail (Coturnix japonica) chicks were used to investigate the effect of feathering rates on growth and slaughter traits. Feathering rates were classified based on the results of stepwise regression using numbers and lengths of both primaries and secondaries and tail length at 7 and 10 days of age as predictors. At 7 and 10 days old, number of primary feathers had phenotypically positive low correlations (rps) with body weight (BW), whereas number of secondaries had positive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The average 5-week-old weight value for Japanese quails in this study is consistent with the findings of some researchers [14,[23][24][25][26], who found the 5-week-old weight of the quails to be between 179.07 g and 190.00 g, which has not been conducted in any genetic improvement study before. Likewise, the mean value for 6-week-old weight found in this study is consistent with the values (200.13-232.4) reported by Lotfi et al [27], Karaman et al [28], and Shafik et al [29].…”
Section: Discussionsupporting
confidence: 92%
“…The average 5-week-old weight value for Japanese quails in this study is consistent with the findings of some researchers [14,[23][24][25][26], who found the 5-week-old weight of the quails to be between 179.07 g and 190.00 g, which has not been conducted in any genetic improvement study before. Likewise, the mean value for 6-week-old weight found in this study is consistent with the values (200.13-232.4) reported by Lotfi et al [27], Karaman et al [28], and Shafik et al [29].…”
Section: Discussionsupporting
confidence: 92%
“…Quails of the selected line significantly had higher carcass %, dressing %, weights of giblets, heart, gizzard and liver (+3.65%, +2.59, 23.79, 68.42, 13.21 and 23.47% respectively) than the CL as shown in Table 4. Similar trend of significant line effect on carcass% was reported by Mahmoud et al (2018). However, Khaldari et al (2010) reported insignificant differences due to lines for carcass%.…”
Section: Performance Of Some Carcass Traits: Line Effect On Carcass Tsupporting
confidence: 74%
“…Selection for high BW42 and GR1-42 significantly improved carcass%, dressing% and boneless meat % of Japanese quail, also the HGR1-42 line had higher carcass%, dressing% and BLM% than other lines as reported by Mahmoud (2006). Mahmoud et al (2018) found significant differences due to lines for dressing%.…”
Section: Performance Of Some Carcass Traits: Line Effect On Carcass Tmentioning
confidence: 91%
“…Furthermore, Taskin et al [ 36 ] found that across selection generations, sex was a substantial source of variance for BW at all ages. On the contrary, Mahmoud et al [ 37 ] found an insignificant sex effect on BW at all ages. In addition, treated quails showed significantly faster GR14–21 and GR14–42 than the untreated group; Zhu et al [ 25 ] and Wei et al [ 26 ] reported similar trends in ducks and chickens.…”
Section: Discussionmentioning
confidence: 90%